Partisipasi Masyarakat dalam Pengembangan Desa Wisata (Studi Kasus Desa Menang Kecamatan Pagu Kabupaten Kediri) - Maya Sajidah Salsabila; Agus Machfud Fauzi (Jurnal Pariwisata Terapan, 2021)
The village won has tourism potential, namely Petilasan Sri Aji Jaya Baya and star fruit. The purpose of this study was to determine community participation in the development of a tourist village in Menang Village which eventually became one of the sources of economic improvement for the surrounding community. The method used in this research is qualitative because it can provide an overview of community participation in the development of a tourist village. The analysis uses Max Weber's theory of rationality. Max Weber's rationality theory can explain community participation in developing tourist villages. Collecting information by means of interviews, observation, and documentation. Based on the research results, there is community participation in the form of ideas, energy, and creativity. This is done by the community to work together to develop the star fruit tourism village in an effort to improve the community's economy.